ANTINEOPLASTIC AND PROTEOMIC SIGNATURE OF SIMVASTATIN TREATED CD44+/ CD24- TRIPLE NEGATIVE BREAST CANCER STEM -LIKE CELLS: Pharmaceutical Science-Pharmacology - JAIKANTH CHANDRASEKARAN; INDHUMATHI THILLAI; PREMA GURUMURTHY; KOTTURATHU MAMMEN CHERIAN (International Journal of Life Science and Pharma Research, 2022)
Simvastatin, a potent HMG CoA reductase inhibitor is gaining significant importance in targeting cancer stem cells. Despites its effects in reducing the expression of CSC surface markers and sphere forming ability in cancer stem cells their molecular mechanism remains poorly understood.In this study we employed label free quantitative proteomic profiling using mass tandem spectroscopy to corroborate the effect of Simvastatin on the cell proliferation, mammosphere formation and its apoptotic effect on CD44+/CD24- Breast Cancer Stem Cells (BCSCs).Simvastatin induces inhibition of cell proliferation in CD44+ CD24- BCSCs. Half inhibitory concentration IC50 was found to be 5 µg/ml. Further Simvastatin induces apoptosis in BCSCs stained with Nexin reagent. Furthermore Simvastatin treatment for 48 hrs with various concentrations significantly inhibited the growth of 6 days old mammospheres in a dose dependent manner. In label free quantitative proteomic profiling of Simvastatin treated and untreated BCSCs, 99 differentially expressed proteins were identified of which, 48 were upregulated and 51 were down regulated. Gene ontology and KEGG pathway enrichment analysis exposed 18 potential pathways associated with Simvastatin treatment. These identified pathways were shown to be related with carcinogenesis, tumor progression, metastasis, focal adhesion and metabolic effects in cancer cells. Among the down regulated proteins Vinculin, Heat shock protein beta-1(HSPB1) was significantly down regulated.Our study reveals that Simvastatin potentially targets BCSCs and their regulatory pathways. Further our proteomics profiling implies the better use of existing drugs and new targets in cancer therapeutics.